1999
DOI: 10.1007/pl00009085
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of lignin peroxidase production from Phanerochaete chrysosporium using response surface methodology

Abstract: The ligninolytic white rot fungus Phanerochaete chrysosporium, holds good promise as a biological treatment tool due to its ability to produce the lignin peroxidase enzyme which has the potential to degrade a wide variety of hazardous compounds. The effective application of this technique requires optimisation of the process variables to maximise the enzyme production. Response surface methodology was applied to determine the effects of glucose, ammonium tartarate and ferrous sulphate and their mutual interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The response surface plots showing the synergistic effects of the selected parameters on the EI of the developed pigeon–pea flour blend were presented in Figure 1. The significance of the interactions is determined by the shape of the response surface, based on the circular or elliptical nature as well as the overall ANOVA values (Manimekalai & Swaminathan, 1999). In Figure 1a, the effect of feed blend composition and feed moisture content on EI at fixed screw speed of 200 rpm (centre point) revealed that EI is dependent on all the factors and their synergistic effect resulted in optimum response, as indicated in Table 2, with a p ‐value of <0.0001.…”
Section: Resultsmentioning
confidence: 99%
“…The response surface plots showing the synergistic effects of the selected parameters on the EI of the developed pigeon–pea flour blend were presented in Figure 1. The significance of the interactions is determined by the shape of the response surface, based on the circular or elliptical nature as well as the overall ANOVA values (Manimekalai & Swaminathan, 1999). In Figure 1a, the effect of feed blend composition and feed moisture content on EI at fixed screw speed of 200 rpm (centre point) revealed that EI is dependent on all the factors and their synergistic effect resulted in optimum response, as indicated in Table 2, with a p ‐value of <0.0001.…”
Section: Resultsmentioning
confidence: 99%
“…The P ‐values are used as a tool to check the significance of each coefficient. The smaller the value of P , the more significant the corresponding coefficient (Manimekalai & Swaminathan, 1999).…”
Section: Resultsmentioning
confidence: 99%